(3YdGbI GdEOGQI GdeOQSjI aj GdJYdje GdQSej GdCSGSj HGdeLJeY GdeMdj aj bVGA YcGQ(B:(3OQGSI ejOGfjI aj GdeOGQS GdeJhSWI GdQSejI aj bVGA YcGQs - (3GdeSdeGfj, eQhGfs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2003)
(3JQJcR gPg GdOQGSI Ydi JTNjU OhQ GdeOjQ aj JWhjQ hJMSjf EfJGLjJg aj eOQSJg, hGdegGe GdJj jDOjgG(B. (3hgj JSGge aj cTa OhQ GdeLJeY aj GdJCKjQ Ydi GdEOGQI GdeOQSjI ef NdGd GdYdGbI GdbGFeI HjfgeG hYf JhbYGJ GdeOjQ hQDjJg ddeLJeY GdeMdj hGdJYdje GdeOQSj(B. (3JgOa GdOQGSI Edi eYQaI GdYdGbI GdbGFeI Hjf GdeLJeY GdeMdj hGdEOGQI GdeOQSjI hfJGFLgG bjGSG HGdJMUjd GdYdej ddWdGH hCOGA GdeYdejf hGdYed Ydi GQJbGA GdEOGQI GdMGdjI HYdGbGJ LjOI JQHWgG eY GdeLJeY GdeMdj ef CLd GSJKeGQ WGbGJg hEecGfGJg GdeGOjI hGdeYfhjI hYdi JMbjb CYdi eSJhi eecf ef JMSjf GdJYdje aj GdeOQSI(B. (3hdJMbjb gPg GdZGjI Je GSJNOGe GdefgL GdhUaj ddhbha Ydi YdGbI GdeOjQ aj GdeOQSI GdQSejI eY GdeLJeY GdeMdj hGdefgL GdJMdjdj GdPj jQJcR Ydi JMdjd GdeYWjGJ GdEMUGFjI aj GdGSJeGQGJ hGdJj HjfJ MLe GdJYGhf GdeGOj hGdeYfhj GdbGFe YedjG Hjf GdEOGQI GdeOQSjI hGdeLJeY GdeMdj(B. (3NdUJ GdOQGSI Edi Cf eOjQj bVGA YcGQ de jJe EYOGOge SGHbG dcj jbhehG HhXjaI GdEOGQI GdeOQSjI hdG jMedhf TgGOGJ GNJUGU aj GdEOGQI GdJQHhjI HGYJHGQ GdEOGQI GNJUGUkG YdeqjkG CcGOjeqjkG(B. (3hQcRJ CjVG Ydi VQhQI GdYhOI Edi cdjI GdJQHjI GdeNhdI QSejG EYOGO GdeOjQjf dcGaI GdeOGQS aj eQGMd GdJYdje GdCSGSj hGdKGfhj(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Akar; Akar; Etablissement scolaire et organisations civiques; Public Sector Intermediate Education; School and civic organizations; Secteur Public Cycle moyen; (3GdJYdje GdQSej GdeQMdI GdeJhSWIs; (3GdeOQSI hGdgjFGJ GdeOfjIs; (3YcGQs